Pharmacological Evaluation of Cedrus Deodara leaves extract on Carbon tetra-chloride induced Hepatotoxicity in Wistar Rats - Joshi, Priya; Dhariyal, Rahul Singh; Singh, Sanjay (Journal of Neonatal Surgery, 2025)
Background: Carbon tetrachloride (CCl₄) is a well-established agent for inducing oxidative liver injury. While Cedrus deodara holds traditional relevance in hepatoprotection, its leaves extract remains scientifically underexplored. This study evaluates the biochemical and histological effects of its methanolic extract in a CCl₄-induced hepatotoxicity model. Methods: Leaves were methanol-extracted via Soxhlet apparatus. Male Wistar rats were divided into five groups: normal control, CCl₄ control, two Cedrus Deodara extract-treated groups (250 and 500 mg/kg, p.o.), and a silymarin (100 mg/kg, p.o.) standard group. Extract and silymarin was administered once daily for 14 days. Hepatotoxicity was induced via CCl₄ (1 ml/kg i.p. 1:1 v/v in olive oil) on Days 7 and 14. Biochemical parameters (SGOT, SGPT, ALP, bilirubin), and liver histopathology were evaluated. Results: CCl₄ significantly elevated hepatic markers. Treatment with C. deodara extract, especially at 500 mg/kg, restored biochemical levels (p < 0.001) and improved hepatic architecture, with outcomes comparable to silymarin. Conclusion: Methanolic leaves extract of C. deodara confers dose-dependent hepatoprotection, likely via free radical scavenging and membrane stabilization. Its safety profile and efficacy validate its traditional use and warrant further pharmacodynamic investigation.